Unmet need for modern contraceptives and associated factors among women in the extended postpartum period in Dessie town, Ethiopia - Masresha Tegegn; Mastewal Arefaynie; Tenaw Yimer Tiruye (BMC, 2017)
Abstract Background The contraceptive use of women in the extended postpartum period is usually different from other times in a woman's life cycle due to the additional roles and presence of emotional changes. However, there is lack of evidence regarding women contraceptive need during this period and the extent they met their need. Therefore, the objective of this study was to assess unmet need for modern contraceptives and associated factors among women during the extended postpartum period in Dessie Town, North east Ethiopia in December 2014. Methods A community-based cross-sectional study was conducted among women who gave birth one year before the study period. Systematic random sampling technique was employed to recruit a total of 383 study participants. For data collection, a structured and pretested standard questionnaire was used. Descriptive statistics were done to characterize the study population using different variables. Bivariate and multiple logistic regression models were fitted to control confounding factors. Odds ratios with 95% confidence intervals were computed to identify factors associated with unmet need. Results This study revealed that 44% of the extended post-partum women had unmet need of modern contraceptives of which 57% unmet need for spacing and 43% for limiting. Education of women (being illiterate) (AOR (adjusted odds ratio) =3.37, 95% CI (confidence interval) 1.22-7.57), antenatal care service (no) (AOR = 2.41, 95% CI 1.11-5.79), Post-natal care service (no) (AOR = 3.63, CI 2.13-6.19) and knowledge of lactational amenorrhea method (AOR = 7.84 95% CI 4.10-15.02) were the factors positively associated with unmet need modern contraceptives in the extended postpartum period. Conclusion The unmet need for modern contraception is high in the study area. There is need to improve the quality of maternal health service, girls education, information on postpartum risk of pregnancy on the recommended postpartum contraceptives to enable mothers make informed choices of contraceptives.